2017
DOI: 10.1093/jee/tox153
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Distance and Population Size of Juvenile Colonies of the Formosan Subterranean Termite (Isoptera: Rhinotermitidae) in Laboratory Extended Arenas

Abstract: The relationship between colony size and foraging distance was examined in extended foraging arenas with juvenile colonies of the Formosan subterranean termite, Coptotermes formosanus Shiraki. Our results showed that as long as royal pairs are present, larger colonies foraged at longer distances, and the oldest workers distributed farther away from the central nest. The results agree with the scaling model that predicts a large foraging range for animals of larger body size. An analysis of published data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Workers from larger colonies moved more forward than those from smaller ones. This is perhaps related to the finding that workers from larger colonies of social insects often forage over larger distances than those from smaller colonies [96][97][98]. Workers were not attracted to the honey reward by smell, as the MST did not differ when honey was offered or not during the first run.…”
Section: Discussionmentioning
confidence: 92%
“…Workers from larger colonies moved more forward than those from smaller ones. This is perhaps related to the finding that workers from larger colonies of social insects often forage over larger distances than those from smaller colonies [96][97][98]. Workers were not attracted to the honey reward by smell, as the MST did not differ when honey was offered or not during the first run.…”
Section: Discussionmentioning
confidence: 92%
“…Molting occurred exclusively in the central nest in all control colonies, which corroborates with the molt-site fidelity in C. formosanus colonies described by Kakkar et al . 11 . Workers traveled from the foraging site to the central nest for molting and stayed inside or in the vicinity until at least 36 h post molting.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Kakkar et al . 11 showed that termites move back to central nest near reproductives and brood to complete the molting process and this molting-site fidelity may offer another explanation for the success of noviflumuron baits to eliminate termite colonies. Because molting took place in the central nest, we hypothesize that noviflumuron-affected termites may die near reproductives and broods instead of the foraging sites, which prevents the aversion of dead termites at bait stations.…”
Section: Introductionmentioning
confidence: 97%
“…temperature (Arab & Costa-Leonardo, 2005;Cornelius & Osbrink, 2011), water (Hu et al, 2012), soil (Evans, 2003;Lima & Costa-Leonardo, 2012), obstacles (Pitts-Singer & Forschler, 2000)] and intrinsic colony needs [i.e. colony growth (Traniello & Leuthold, 2000), colony size (Su et al, 2017)] as well as by resource offer. The inverse relationship between resource density and foraging area has also been shown in ants (Brown & Gordon, 2000;Leal & Oliveira, 2000;Urbas et al, 2007) and other eusocial insects (see Richter, 2000;Westphal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%